PERENCANAAN MANAJEMEN KONSTRUKSI GEDUNG KANTOR BERSAMA 4 LANTAI DI JALAN SEPAKAT II KOTA PONTIANAK - zuhri, muhammad d; Juliawan, Roy; Utomo, satriyo; Resky, Indah Anjar (RETENSI, 2024)
This Final Project is a construction management planning that includes 5 aspects, namely starting from Cost Management, Time, Human Resources, Quality, and K3. This Final Project aims to enable the author to explore and understand more about the aspects of construction management planning. Construction management itself is a science that studies and practices the managerial and technological aspects of the construction industry. Construction management can also be interpreted as a business model carried out by construction consultants in providing advice and assistance in a development project. The planning method for construction management starts from collecting data on specifications, analyzing the unit price of work, and also based on the Regulation of the Minister of PUPR in 2022 to the instructions for implementing K3 in construction. Then the results of management planning can be concluded that the required cost budget, the duration of time used during construction, the number of workers involved in the construction project, the quality that ensures the quality of construction, and the prevention of potential hazards as a priority for Occupational Safety and Health.